Vaccination coverage of children with chronic diseases is inadequate especially for specifically recommended vaccines. (27th April 2020) - Diallo, Diariatou; Santal, Claire; Lagrée, Marion; Martinot, Alain; Dubos, François
Abstract: Aim: Our objectives were to measure the vaccine coverage rates for children with chronic diseases as well as the prevalence of potentially harmful delays for generally recommended vaccines. We also identified the factors influencing non‐adherence to vaccines specifically recommended for chronic conditions. Methods: Three non‐interventional point‐prevalence surveys were performed in 2014 in all paediatric units at Lille University Hospital among children aged 2 months‐18 years with chronic diseases and vaccination data. Vaccine coverage and delays for generally recommended vaccines were studied. The children who were up‐to‐date and those under‐vaccinated for specifically indicated vaccines were compared and the factors potentially associated with under‐vaccination were studied with multivariable analysis. Results: We screened 682 patients: of 207 with chronic diseases, mainly neurological, muscular and respiratory disorders, 146 had vaccination data. Only 47% (95% confidence interval 39‐55) were up‐to‐date for all generally recommended vaccinations; potentially harmful vaccination delays were high (26%‐75%). Only 11% of the 81% of patients for whom some vaccines were specifically recommended were up‐to‐date. Low maternal education level was significantly associated with under‐vaccination (adjusted odds ratio 10.5, 95% confidence interval 1.3‐86.9, P  = .03). Conclusion: This study showed inadequate vaccine coverage rates and significant delays among children with chronic diseases.